Pengembangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada Sekolah Dasar Adhyaksa - Ilham Fahrozi; Satria Oldie Versileno; Sulistia Ramadhani; Errissya Rasywir (TIN: Terapan Informatika Nusantara, 2022)
SD Adhyaksa 1 JAMBI, one of the educational institutions located in Jambi City, whose online registration process is still through the Google form. Management starts from the admin who receives the Google form after which it is inputted again into Microsoft Excel. So that some obstacles arise because they still use the manual method which takes time to process. The system currently used by SD Adhyaksa 1 Jambi Elementary School is registration of new students by first coming to the school to check the registration schedule and filling out the form provided by the committee. This study aims to design a website-based new student registration system (PSB) at SD Adhyaksa 1 Jambi Elementary School to make it easier for prospective students to register. The results of this study indicate that the system can manage the process of admitting new students at SD Adhyaksa 1 Jambi Elementary School using PHP and MYSQL. The results of this study are an application that can help solve problems that exist at SD Adhyaksa 1 JAMBI in registering new students to making reports